On the high resolution regional weather forecast model (HRM) and forecasting tropical cyclone motion over the south china sea - Duc, Le; Thang, Le Cong; Xin, Kieu Thi (Vietnam Journal of Mechanics, 2005)
Chan (1995) [2] has found that, only 70% in 60 cases of the tropical cyclone (TC) movement test (TMT-90) developed from steering flows. The 30% remain of cases have to be explained by nonbarotropic processes. We are of the opinion that all weak, slow-moving and unexpected changing TCs over the South China Sea are in this 30% set. The nonlinear interaction between barotropic and nonbarotropic processes has affected on motion and structure of such TCs. In this paper, we use the high resolution weather forecast model (HRM), which is able to simulate meso-scale phenomena in limited regions, to predict motion of TCs in the South China Sea in 2002-2004, including two typical weak, slow-moving and unexpected changing TCs Mekhala and Nepartak. We have chosen two forecast domains with different areas and resolutions. The results show that with the smaller domain, appropriate buffer and higher resolution HRM can predict better motion of TCs operating in the South China Sea.